Lotion deodorant formulation of ethanolic extract of red betel leaf (Piper crocatum Ruiz & Pav) with stearic acid as base - Lidia Lidia; Ensiwi Munarsih; Dini Aprilianti (Universitas Islam Indonesia, 2022)
Abstract Background: Red betel leaf (P. crocatum Ruiz & Pav) possesses antibacterial properties, so the prospect is to be developed as a deodorant in lotion dosage forms.Objective: This study was conducted with the intention to prepare, evaluate, and investigate the stability of deodorant lotion preparations from the ethanolic extract of red betel leaf (P. crocatum Ruiz & Pav) based on stearic acid.Methods: The maceration method used 70% ethanol as solvent to obtain red betel leaf extract. Furthermore, the concentrated extract was formulated as a deodorant lotion formula into three formulas, FI, FII, and FIII, with varying concentrations of stearic acid 2, 4, and 6%, respectively. All the deodorant lotion formulas were evaluated, their characteristics and stability of organoleptic, pH, homogeneity, viscosity, spreadability, adhesion, and irritation properties. The physical stability test was done by cycling test. The storage stability test was evaluated for 28 days.Results: Evaluation of physical properties for 28 days showed that deodorant lotion was homogeneous and pH in the range of 5.5-6.4; viscosity, spreadability, and adhesion tests gave good results and stability. In the irritation test, all formulas showed no irritation. Statistical test paired T-test on stability testing during storage and cycling test showed that the best and most stable formula was F3 with 6% stearic acid concentration.Conclusion: Ethanolic extract of red betel leaf (P. crocatum Ruiz & Pav) can be formulated into a deodorant lotion preparation that is stable and good during storage.Keywords: deodorant lotion, Piper crocatum Ruiz & Pav, stearic acid Intisari Latar belakang: Daun sirih merah (Dasimer) (P. crocatum Ruiz & Pav) berkhasiat sebagai antibakteri, sehingga prospek untuk dikembangkan sebagai deodorant dalam bentuk sediaan losion.Tujuan: Penelitian ini dilakukan dengan tujuan untuk membuat, mengevaluasi dan melakukan uji stabilitas sediaan losion deodoran dari ekstrak etanol Dasimer (P. crocatum Ruiz & Pav) dengan variasi basis asam sterat.Metode: Ekstrak Dasimer diekstraksi menggunakan metode maserasi dengan etanol 70% sebagai pelarut. Ekstrak kental etanol yang diperoleh diformulasikann menjadi 3 formula losion yaitu FI, FII dan FIII dengan variasi asam stearate 2, 4 dan 6 %. Formula losion deodoran, dievaluasi karakteristik dan stabilitasnya meliputi organoleptis, homogenitas, pH, viskositas, daya sebar, daya lekat dan iritasi. Uji stabilitas fisik dilakukan dengan cycling test. Uji stabilitas dalam penyimpanan dievaluasi selama 28 hari.Hasil: Evaluasi sifat fisik selama 28 hari menunjukkan bahwa deodoran losion homogen dan pH dalam rentang yang baik yakni 5,5-6,4. Pengujian viskositas, daya sebar dan daya lekat juga memberikan hasil yang baik dan stabil. Pada pengujian iritasi, semua formula menunjukkan tidak terjadi iritasi. Uji statitistik T-test berpasangan pada pengujian stabilitas selama penyimpanan dan cycling test, menunjukkan bahwa formula yang paling baik dan stabil yaitu F3 dengan konsentrasi asam stearat 6 %.Kesimpulan: Ekstrak etanol Dasimer (P. crocatum Ruiz & Pav) dapat dibuat menjadi sediaan deodoran losion yang stabil dan baik pada saat penyimpanan.Kata Kunci: losion deodoran, Piper crocatum Ruiz & Pav, asam stearat